Refraksi Pengaturan Sanksi Pidana Atas Perbuatan Merendahkan Kehormatan Dan Keluhuran Martabat Hakim di Indonesia - Gayatri, Ni Komang Cinmaya; Pramita, Kadek Sista Pradnya; Putra, I Putu Aris Perdana; Dwi Cahyadhi, I Dewa Gede Agung; Pradnya Dewi, Gusti Ayu Agung Nadya (Kertha Patrika; Vol 46 No 2 (2024)DO - 10.24843/KP.2024.v46.i02.p07, 2024)
This research was conducted using a normative legal research method to identify the ambiguities surrounding the minimization of criminal acts against judges, which can be further clarified in legislation so that judges do not feel hesitant or reluctant to report criminal actions committed by irresponsible individuals. Judges, who hold the most respected dignity in court proceedings, often become victims of the decisions they render. One notable case involved a Chief Judge at the Lumajang Religious Court who experienced violence when the defendant threw a chair while the judge was reading the verdict. The lack of clear options for resolving cases involving actions that demean judges is the primary reason why judges are reluctant to report to the Judicial Commission, leading to unnecessary prolongation of cases or resolution through non-litigation channels. This research highlights the ambiguity of legal protection for judges against actions that demean their honor and dignity by comparing the unclear norms regarding the offense of demeaning the honor and dignity of judges in the Criminal Code (KUHP) with other legislative regulations.